Re-establishment of a centuries-old synonym forgotten in Pisonia with fleshy anthocarps and its transfer to Guapira (Nyctaginaceae: Pisonieae) - Rossetto, Elson Felipe Sandoli; Costa, Daniel Silva; Braga, João Marcelo Alvarenga (Phytotaxa, 2025)
N/A